2017
DOI: 10.1007/s10571-017-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression in the Locus Coeruleus-Amygdala Circuitry in Inhibitory Avoidance PTSD Model

Abstract: The locus coeruleus (LC)-amygdala circuit is implicated in playing a key role in responses to emotionally arousing stimuli and in the manifestation of post-traumatic stress disorder (PTSD). Here, we examined changes in gene expression of a number of important mediators of the LC-amygdala circuitry in the inhibition avoidance model of PTSD. After testing for basal acoustic startle response (ASR), rats were exposed to a severe footshock (1.5 mA for 10 s) in the inhibitory avoidance apparatus. They were given con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
1
16
1
Order By: Relevance
“…CREB is a transcriptional factor which regulates transcription of multiple downstream genes including c-Fos, brain-derived neurotrophic factor (BDNF), tyrosine hydroxylase (TH), and neuropeptides [ 130 , 131 ]. These observations corroborate other studies that have shown altered expression of trophic factors and NE synthetic enzymes [ 18 , 28 , 54 57 , 61 ].…”
Section: Lc/ne Synaptic Plasticity Changes During Stresssupporting
confidence: 92%
See 2 more Smart Citations
“…CREB is a transcriptional factor which regulates transcription of multiple downstream genes including c-Fos, brain-derived neurotrophic factor (BDNF), tyrosine hydroxylase (TH), and neuropeptides [ 130 , 131 ]. These observations corroborate other studies that have shown altered expression of trophic factors and NE synthetic enzymes [ 18 , 28 , 54 57 , 61 ].…”
Section: Lc/ne Synaptic Plasticity Changes During Stresssupporting
confidence: 92%
“…These effects are of particular interest in LC, where the interaction of CRF with its receptor CRFR1 activates cAMP-dependent intracellular signaling cascades, increasing tonic discharge and promoting anxiety-like behavior [ 64 , 77 , 188 , 189 ]. Evidence suggests that chronic stressor exposure is able to alter LC gene expression [ 18 , 28 , 54 57 , 61 ], promote long-term changes in synaptic transmission and excitability [ 53 , 62 ] and receptor trafficking [ 58 60 , 185 ], and, importantly, induce morphological changes and dendritic remodeling ( Figure 1 ) [ 50 , 52 , 53 , 57 , 190 ]. These actions appear to be dependent on a number of kinases and GTPases and their associated signaling pathways [ 50 , 52 , 57 ] and potentially on AMPAR function [ 191 , 192 ] which is modulated by CRF in the short term [ 49 ] and stressor exposure in the long term [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the medical staff in the experimental group had higher somatization symptoms, depression symptoms, and symptoms related to post-traumatic stress disorder. Clinical studies have found that under stress, the neuroendocrine network regulated by the HPA axis in the patient's body is disordered, the level of corticotropin-releasing factor is increased, and the level of cortisol is low, leading to the continuous activation of the adrenergic pathway [16]. As a result, emotions such as anxiety, fear, irritability, and hypersensitivity are more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Advances on the role of specific circuits during stress include a report on alterations in gene expression in the locus coeruleus-amygdala circuitry during stress (Sabban et al 2017) and the role of the nucleus of the solitary tract/ dorsal vagal complex (Herman 2017).…”
mentioning
confidence: 99%